IMPLEMENTASI PEMBELAJARAN TAHASSUS DI MA MA’ARIF 1 JOMBANG - Nurul Indana; Noor Fatikah; Irma Muniroh (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
Discussions about education, it is impossible to be free from the object that is the target, namely humans. Allah SWT created humans to be the most noble creatures among the creatures He created. Each educational institution has its own learning system in achieving learning objectives. However, there are also educational institutions that have their own way of achieving learning goals, one of which is learning and memorizing Juz 30, Surat Yaasin, tahlil, namely by developing takhassus programs which can make students who have better personalities, strengthen values. the character possessed by students so that they become complete human beings, both soul, body, intellectual and personality. So, students are not only focused on general knowledge but also deepen their religious knowledge so that they are able to become human beings who have strong faith qualities. The purpose of this study is to describe the process of implementing the Tahassus program at MA Ma'arif 1 Jombang. The results showed that the Tahassus program could improve reading and writing of the Qur'an, including increasing religious knowledge and as a provision when entering the community.